Internal agricultural policy of the government of A. V. Kolchak - E. A. Koshechkina (Омский научный вестник: Серия "Общество. История. Современность")
The article highlights some aspects of theoretical and practical actions of A. V. Kolchak in the agrarian and peasant question. The author shows how the proclaimed Russian government sought to attract to its side the most significant segment of the country’s population, to regulate social relations constructing a special form of relations with the peasantry. The article deals with attempts to introduce new agricultural legislation, considers unrealized projects of agrarian reforms, and highlights the reasons for the defeat of the government of A. V. Kolchak. The author considers the problem of preserving the principles of land ownership with the postponement of registration of legal papers and not implementing the proposed projects as one of the main reasons for the defeat of A.V. Kolchak in particular and the White movement in general. This circumstance eventually secured the victory of Bolshevism